Solidification of phase change materials in horizontal annuli. (January 2023) - Azad, Mohammad; Groulx, Dominic; Donaldson, Adam
Abstract: This paper presents experimental results on solidification of n -octadecane and dodecanoic acid in horizontal annuli with 18-, 27-, and 36-mm center tubes and a 127-mm outer cylinder. Dodecanoic acid was superheated to 2.5 °C above the solidification temperature and n -octadecane was superheated by 2.5 or 37.5 °C. Dodecanoic acid was solidified from the center tubes at temperatures 8.44, 21.1, or 33.8 °C below the solidification temperature; these temperatures for n -octadecane were 8.44 or 21.1 °C. Additionally, the solidification of dodecanoic acid was studied under the conditions of consecutive melting and solidification, where it was subcooled by 2.5 °C and the superheating was dictated by the melting conditions. For these cases, the melting/solidification temperature differentials were 16.9 or 33.8 °C above/below the melting/solidification temperature. A comparative study of melting and solidification of n -octadecane was also done. For the melting experiments, n -octadecane was subcooled by 2.5 °C and melted at 21.1 °C above the melting temperature, which was compared to the respective solidification experiments. The volumes of solid/liquid PCMs per unit length of the enclosures and the positions of solid-liquid interfaces were obtained photographically. The results show that the solidification rates can be enhanced by using a larger center tube, solidifying the PCM at a lower temperature, and using PCMs initially liquid close to the solidification temperature. The effects of these parameters are greater on the solidification of n -octadecane than dodecanoic acid. The effects of PCMs on the solidification process depend on how strong the conductive heat transfer is. The results also show that up to 30 % (if not more) of solidification can be contributed by natural convection in the early stages of the solidification process. Highlights: The solidification of dodecanoic acid and n -octadecane in horizontal annuli was studied experimentally. The impact of initial and final temperatures was tested. Conduction dominated the heat transfer process, but convection could contribute up to 30 % to the heat transfer. Initially superheating of the PCM greatly affects solidification in the early stages.